1997
DOI: 10.1161/01.cir.95.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Implications of Reocclusion on Left Ventricular Size and Function After Successful Thrombolysis for First Anterior Myocardial Infarction

Abstract: Background Successful thrombolysis can prevent left ven tricular dilatation after acute myocardial infarction. However, in almost 30% of patients, reocclusion occurs. The aim of this study was to assess the long-term implications o f reocclusion on left ventricular size and function.Methods and Results Fifty-six patients were studied with two-dimensional echocardiography at baseline (2 ± 1.6 days) and 5.0± 1.4 years after first anterior myocardial infarction. All pa tients (a subset of those enrolled in the AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 53 publications
(12 reference statements)
0
19
1
Order By: Relevance
“…18 Left ventricular volumes in end-diastole and end-systole were determined, using a system for off-line analysis (ImageVue, Nova Microsonics Inc., NJ, USA) using Simpson's biplane method. 19 Doppler measurements were also analysed with this system.…”
Section: Analysis Of Echocardiographymentioning
confidence: 99%
“…18 Left ventricular volumes in end-diastole and end-systole were determined, using a system for off-line analysis (ImageVue, Nova Microsonics Inc., NJ, USA) using Simpson's biplane method. 19 Doppler measurements were also analysed with this system.…”
Section: Analysis Of Echocardiographymentioning
confidence: 99%
“…We cannot, however, exclude that a later follow-up would have given different results. Indeed, in a recent analysis of a subset of the patients enrolled in the APRICOT study, Nijland et al 24 have shown that late reocclusion of the IRA is associated with left ventricular dilatation 5 years after first MI.…”
Section: Late Reocclusion and Left Ventricular Functionmentioning
confidence: 99%
“…Second, it is also possible that, as shown in previous trials [5], this mortality reduction was a result of a reduction in reocclusion with stent use [11]. Several studies have suggested that sustained patency was associated with better left ventricular remodeling (less left ventricular dilatation), improved electrical stability, and the provision of collateral vessels to other coronary beds for protection against future events [12,13]. In fact, infarct-related artery patency at 6 months is strongly associated with long-term survival (6 years) after MI [14].…”
Section: Discussionmentioning
confidence: 93%